Deprivation of Basic Needs and Denial of the Human Rights: Breaking the Nexus in Urban Poor Families in Bangladesh - Fatema, Nuzhat; Murtaza, Md Ghulam (Journal of Bangladesh Institute of Planners, 2020)
Abstract Not Available JBIP, Vol. 13, 2020 (Printed in June 2021), pp.111-120